Saving Decisions as a Consequence of Product and Service Quality Excellence in Savings and Loans Cooperatives and Sharia Financing (Study on Customers of Bmt Bina Ihsanul Fikri, Bugisan Yogyakarta Branch) - Nelly Amalia Mahmudah; Salamatun Asakdiyah; Fitroh Adhilla (www.amertainstitute.com, 2024)
This research aims to determine the influence of Product Excellence and Service Quality on Customer Saving Decisions at the BMT Bina Ihsanul Fikri Office, Bugisan Branch, Yogyakarta. The population in this study was 120 customers, with a sampling technique using purposive sampling. The sample used was all 120 BMT Bina Ihsanul Fikri customers, Bugisan Branch, Yogyakarta. The data used in this research is primary data obtained through filling out questionnaires. To analyze the data, multiple linear regression analysis tools were used. The research results show that Product Excellence and Service Quality have a significant influence on customers' Saving Decisions at BMT Bina Ihsanul Fikri, Bugisan Branch, Yogyakarta. Product Excellence has a regression coefficient (B) of 0.179 with a significance level of 0.000, while Service Quality has a regression coefficient (B) of 0.576 with a significance level of 0.000. This shows that these two variables make a positive and significant contribution to customers' savings decisions. This research provides empirical evidence that increasing product excellence and service quality can encourage customers' decisions to save, so BMT is expected to continue improving these aspects to increase customer satisfaction and loyalty.